2009
DOI: 10.1111/j.1360-0443.2009.02731.x
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of quitting smoking: findings from the International Tobacco Control (ITC) Four Country Survey

Abstract: Aims To describe the long-term natural history of a range of potential determinants of relapse from quitting smoking. Design, setting and participants A survey of 2502 ex-smokers of varying lengths of time quit recruited as part of the International Tobacco Control (ITC) Four Country Survey (Australia, Canada, UK, USA) across five annual waves of surveying. Measurements Quitters were phone interviewed at varying durations of abstinence, ranging from one to 1472 days (about 4 years) post quitting. Smoking-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
49
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 47 publications
5
49
0
1
Order By: Relevance
“…Examination of the timelines of Expectancy, Purposefulness, and craving to smoke craving remained relatively stable from 2 weeks post-quitting through the 16th week of the study in pregnant women continuing to smoke, whereas these aspects of craving decreased in pregnant smokers who were abstinent. The current analysis suggests no distinction between pregnant smokers and the general population of smokers for changes in craving over time; during smoking abstinence, craving decreases, and during a failed quit attempt, it does not, consistent with studies of non-pregnant smokers(Berlin et al, 2011, 2013, Herd and Borland 2009). Indeed, researchers (Heil et al, 2006 have posited that the rationale for using nicotine replacement therapy (NRT) with pregnant smokers was supported by the characterization of craving and withdrawal as salient predictors of relapse in the general sample of smokers.…”
supporting
confidence: 67%
“…Examination of the timelines of Expectancy, Purposefulness, and craving to smoke craving remained relatively stable from 2 weeks post-quitting through the 16th week of the study in pregnant women continuing to smoke, whereas these aspects of craving decreased in pregnant smokers who were abstinent. The current analysis suggests no distinction between pregnant smokers and the general population of smokers for changes in craving over time; during smoking abstinence, craving decreases, and during a failed quit attempt, it does not, consistent with studies of non-pregnant smokers(Berlin et al, 2011, 2013, Herd and Borland 2009). Indeed, researchers (Heil et al, 2006 have posited that the rationale for using nicotine replacement therapy (NRT) with pregnant smokers was supported by the characterization of craving and withdrawal as salient predictors of relapse in the general sample of smokers.…”
supporting
confidence: 67%
“…For example, men seem to experience lower craving than women in some studies (Elman et al, 2001;Robbins et al, 1999;Saladin et al, 2012;Yu et al, 2007), while individuals with higher impulsivity or novelty seeking traits tend to have higher craving levels (Franken, 2002;Papachristou et al, 2012;Powell et al, 1992;Zilberman et al, 2003). Craving ratings are also influenced by substance use characteristics such as levels of use, duration of abstinence, or dependence severity (Herd and Borland, 2009;Hughes, 1992;Watson et al, 2010), and by period of assessments relative to the target quit date (Hughes, 1992;McCarthy et al, 2006). Given the growing role of EMA in clinical research, but also important variation in findings, the objective of this systematic review was to: (1) assess the link between craving and substance use in all published studies using EMA; and (2) identify the relevant moderators of this relationship among substance users.…”
Section: Introductionmentioning
confidence: 94%
“…were drawn from established psychosocial models of health behaviour (refer to Fong et al (23)) and have been used in past research exploring predictors of quitting (24). Responses to each item were recorded on four- or five-point Likert scales (for more details of each measure see Herd et al (13)).…”
Section: Methodsmentioning
confidence: 99%
“…Results in the corresponding trends paper (13) found that the majority of proposed predictors of relapse changed according to a logarithmic or square-root function. Therefore, for duration of abstinence in the current study, we used the transformation that best fitted each of the dependent variables in the previous paper; a log transformation of days quit was used for proposed predictors that changed over time according to a log function and a square root transformation was used for those that changed according to a square root function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation